309 Mechanical Thrombectomy for Acute Basilar Artery Occlusion, Where Do We Stand? A Safety and Efficacy Analysis. (April 2023) - Abbas, Rawad; Chen, Ching-Jen; Atallah, Elias; El Naamani, Kareem; Herial, Nabeel; Gooch, Michael; Jabbour, Pascal; Rosenwasser, Robert H.; Tjoumakaris, Stavropoula I.
Abstract : INTRODUCTION: Acute basilar artery occlusion accounts for 1% of all ischemic strokes, but more often than not, leads to devastating neurological injury and mortality. Many institutions still opt for best medical therapy for this type of ischemic stroke, however there is increasing evidence that mechanical thrombectomy for these patients leads to better outcomes. METHODS: This study was a retrospective chart review of a prospectively maintained database for patients with acute basilar artery occlusion treated with mechanical thrombectomy from January 2014 through March 2022. RESULTS: Our study included a total of 74 patients. The mean age was 62.7 years and 55.4% were male. The most common comorbidity was hypertension (73%). The mean door to puncture time was 75 minutes and the mean procedure time was 54 minutes. 86.5% of patients had a good mTICI score (≥ 2b). There were 4 patients who had procedural complications, and symptomatic intracerebral hemorrhage occurred in 3 patients. At 90 days, 62.5% of patients had a favorable functional outcome (mRS, 0 – 3). The mortality rate was 32.4% and 2% during the hospital admission and at 90 days respectively. Finally, on univariate analysis, the need for adjunct treatment and higher presenting NIHSS score was associated with poor functional outcome at 90 days (p-value, 0.03 and <0.001 respectively). Shorter procedure time was associated with better revascularization (mTICI score ≥ 2b) (p-value, 0.0015). CONCLUSIONS: Our findings showed that MT is safe and effective for patients presenting with acute basilar artery conclusion and is in conjunction with previous literature. Final results from upcoming trials should hopefully establish MT as gold standard for these patients.